Sex differences in 5-year risk of major adverse cardiovascular events in patients with coronary artery disease and elevated lipoprotein(a) levels - R. B. Alieva; A. B. Shek; A. A. Abdullaev; H. G. Fozilov; Sh. U. Khoshimov; G. D. Abdullaeva; D. Zakirova; L. E. Kan; A. R. Kim; R. A. Kurbanova; D. B. Yusupalieva (Российский кардиологический журнал, 2025)
Aim. To evaluate 5-year major adverse cardiovascular events (MACE) in patients with coronary artery disease (CAD) and high lipoprotein(a) (Lp(a)) levels in the Uzbek population.Material and methods. The study included 216 patients (96 men and 120 women) hospitalized with a diagnosis of "CAD. Progressive angina", in whom MACE (cardiovascular death, non-fatal myocardial infarction and stroke) was assessed during 5 years of follow-up. The 2-∆∆Сt value, correlating with the number of LPA KIV-2 repeats, was determined in genomic DNA using quantitative real-time polymerase chain reaction (qPCR).Results. In patients with CAD with elevated Lp(a) in the quartile 4 ≥48 mg/dL, the MACE risk was 2 times higher (relative risk 2,0; 95% confidence interval 1,04-3,87, P<0,05) than in quartile 1 ≤6 mg/dl. Moreover, among men it was 2,6 times higher (P<0,05), while in women — 1,4 times higher without significant difference. In contrast, in the study cohort, the MACE risk in quartile 1 <3,9 of 2-∆∆Сt was 3 times higher than in quartile 4 (>6) (P<0,01) in men, and 3,3 times higher among women (P<0,05). Lp(a) concentration in the examined subjects was inversely dependent on the 2-∆∆Сt value. We also observed a decreased MACE risk in women with high Apolipoprotein A-I (apoA) levels in quartile 4 (>175 mg/dL) versus quartile 1 (<140 mg/dL) with relative risk of 0,30 (95% confidence interval 0,10-0,98, P<0,05).Conclusion. The 2-∆∆Сt value in the lower quartile associated with a low number of LPA KIV-2 repeats more accurately reflects the MACE risk in women with CAD. Also, the relative risk in women was lower in the upper quartile of apoA compared to the lower one.